METALLIC AND ANTIOXIDANT ENZYMES COMPOSITION OF THE BONES AND MUSCLES OF SOME COMMERCIAL FISH SPECIES IN OJO LAGOON, LAGOS - HAMMED , A. M; AMOSU, A. O.; ISSA, A. O.; BABALOLA, O. A.; SANUTH, M. A.; ADETAYO, M. R.; SAPARA, G. C. (Nigerian Journal of Fisheries, 2024)
This study investigated the metallic composition of Zinc (Zn), Cupper (Cu), Phosphorus (P), Manganese (Mn), Lead (Pb), Iron (Fe), and Magnesium (Mg) and antioxidant enzymes [Super Oxide Dismotase (SOD), Catalase (CAT), Glutathioninie (GSH) and Malanoaldehyde (MDA)] activities in the bones and muscles of four freshwater fish species sourced from fish mongers in Ojo Lagoon landing site, Lagos State. The fishes (Coptodon zillii, Heterobranchus bidorsalis, Clarias gariepinus and Chrysichthys nigrodigitatus) were stored on ice at 4oC and analyzed at the Biochemistry and Pharmaceutical Laboratory Section of the College of Medicine University of Lagos, Idi-Araba, Lagos, Nigeria. Heavy metals were analyzed using Atomic Absorption spectroscopy (AAS), while antioxidant enzyme activities was determined using the supernatant (20%) and a specified hydrogen peroxide volume with a catalase inhibitor. Results showed significant difference (P<0.05) among metals and antioxidants in all studied fish samples except for SOD activity in their muscles. The order of metallic concentrations in the fish tissues was Fe>Mn>Mg>P>Pb>Cu>Zn, with Mg, Pb, and Mn concentrations recorded higher than the permissible limits for consumption as recommended by standard organization such as FAO, FEPA and WHO. C. zillii muscle recorded the highest values of SOD and GSH, and the muscles of C. nigrodigitatus and C. gariepinus were highest in CAT and MDA respectively. The bone of C. nigrodigitatus had the highest GSH, CAT, and MDA activities and C. zillii recorded the highest SOD activity. The study concluded that the fish were nutritionally unhealthy and unsafe for human consumption and, as such not recommended for inclusion in the diet.